2018
DOI: 10.1088/1475-7516/2018/08/019
|View full text |Cite
|
Sign up to set email alerts
|

Searching for dark matter annihilation from individual halos: uncertainties, scatter and signal-to-noise ratios

Abstract: Individual extragalactic dark matter halos, such as those associated with nearby galaxies and galaxy clusters, are promising targets for searches for gamma rays from dark matter annihilation. We review the predictions for the annihilation flux from individual halos, focusing on the effect of current uncertainties in the concentration-mass relation and the contribution from halo substructure, and also estimating the intrinsic halo-to-halo scatter expected. After careful consideration of recent simulation result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 134 publications
0
15
0
Order By: Relevance
“…Not only is the central density of haloes important to halo disruption predictions, it also has implications for the dark matter annihilation boost factor (e.g. Okoli et al 2018;Drakos et al 2019b), as we will explore in Paper III. We also note that our model may not capture decreased central density due to heating, though we suspect that neglecting this is valid, as it has been found that the central regions of haloes are adiabatically shielded from heating (Weinberg 1994a,b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only is the central density of haloes important to halo disruption predictions, it also has implications for the dark matter annihilation boost factor (e.g. Okoli et al 2018;Drakos et al 2019b), as we will explore in Paper III. We also note that our model may not capture decreased central density due to heating, though we suspect that neglecting this is valid, as it has been found that the central regions of haloes are adiabatically shielded from heating (Weinberg 1994a,b).…”
Section: Discussionmentioning
confidence: 99%
“…An issue of particular importance is the long-term survival of the very smallest structures over many orbital periods, as these can dominate the overall annihilation rate (e.g. Okoli et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This is a puzzle, given previous results suggesting the central density must drop as haloes grow. Therefore mergers seem unlikely to cause the evolution of halo central density needed to explain results from cosmological simulations, as pointed out by Okoli et al (2018). Our future work will explore more complicated and more realistic merger scenarios, to see if the trends found in this paper still hold in a cosmological setting.…”
Section: Discussionmentioning
confidence: 62%
“…A second piece of evidence comes from simulations of the first haloes by Ishiyama (2014). Evolving these down to a final redshift of z = 32, he found central densities that were once again much higher at fixed physical radius than expected from extrapolations of the low-redshift concentration-mass-redshift relations; if these densities are conserved, they would increase estimates of the boost factor by up to two orders of magnitude (Okoli et al 2018). From both these studies, the implication is that there must be some mechanism that rearranges the central parts of haloes, causing the mass distribution to expand, and decreasing the central density.…”
Section: Introductionmentioning
confidence: 99%
“…• boost is the increase in collision rate due to the clumping of the dark matter into sub-halos, which we crudely estimate from references [26], [27] and [28]. These papers contain computer simulations of gravitational interactions between dark matter constituents in galactic halos forming clumps of much higher density than the average density.…”
Section: Pos(corfu2019)049mentioning
confidence: 99%